2002
DOI: 10.1038/labinvest.3780408
|View full text |Cite
|
Sign up to set email alerts
|

VASA Is a Specific Marker for Both Normal and Malignant Human Germ Cells

Abstract: SUMMARY:VASA is so far the only known gene in mammals whose expression is specific for the germ cell lineage. We investigated the presence of VASA mRNA and protein in a series of germ cell tumors of different histologic subtypes and anatomic location, as well as in nongerm cell tumors such as testicular lymphomas and Leydig cell tumors. We detected VASA mRNA (by quantitative RT-PCR) and protein (by immunohistochemical staining) in normal spermatogenesis, seminoma (both classic and spermatocytic), carcinoma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 44 publications
(46 reference statements)
5
26
0
Order By: Relevance
“…Therefore, VASA is currently the first definitive genetic marker for distinguishing fetal germ cells from hESCs [57]. As a result, identification of robust levels of VASA protein expression in CIS lends support to the hypothesis that CIS is derived from fetal germ cells that retain high levels of pluripotent stem cell gene expression as well as germ cell-identity markers including VASA [61].…”
Section: Turning Germ Cells Into Germ Cell Tumors: Elevated Expressiomentioning
confidence: 79%
“…Therefore, VASA is currently the first definitive genetic marker for distinguishing fetal germ cells from hESCs [57]. As a result, identification of robust levels of VASA protein expression in CIS lends support to the hypothesis that CIS is derived from fetal germ cells that retain high levels of pluripotent stem cell gene expression as well as germ cell-identity markers including VASA [61].…”
Section: Turning Germ Cells Into Germ Cell Tumors: Elevated Expressiomentioning
confidence: 79%
“…Spermatocytic seminoma may be confused with classical seminoma; the distinction is important from the clinical standpoint because spermatocytic seminoma virtually never metastasises [20,29,56] and requires no treatment besides orchiectomy [7,14,33,45,47,53,57]. Recent immunohistochemical and molecular studies [42,51,59] have demonstrated a different origin for seminoma/ dysgerminoma and spermatocytic seminoma. Seminoma/ dysgerminoma originates from an embryonic germ cell, whilst the cell of origin of spermatocytic seminoma is at least capable of maturing to the stage of spermatogoniapachytene spermatocyte.…”
Section: Discussionmentioning
confidence: 98%
“…Third, they may differentiate into Oct4 and MVH-negative tissues. In nonseminomatous GCTs including teratomas, germ cells have variable or no expression of Oct4 or Vasa (Honecker et al, 2006, Zeeman et al, 2002. Lastly, they could differentiate into somatic lineages.…”
Section: Discussionmentioning
confidence: 99%